STRATEGI PENGEMBANGAN POTENSI MANUSIA (JISM, FITRAH, AKAL, QALB, NAFS) DALAM FilSAFAT PENDIDIKAN ISLAM DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM KONTEMPORER - Shokhekul Huda; Nur Hidayat; Yasin Baidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research explains the nature of human potential (jism, fitrah, reason, qalb and nafs), development strategies and their relevance in contemporary education. Human potential should be understood as an important aspect to detail its characteristics which are then synthesized in the realm of education and development strategies that direct human potential accurately and precisely in the realm of contemporary education. This research aims: 1) To examine the nature of human resources (jism, fitrah, reason, qalb and nafs) by detailing their characteristics. 2) Examining strategies for developing human potential in Islamic Education philosophy. 3) knowing the relevance of human potential in contemporary education. Data collection methods include books and journals. The data analysis technique uses a deductive philosophical method by examining various sources by synthesizing from general to specific. The results of the research are in the realm of human potential: 1) jism helps channel one's character through physical strength, 2) natural innate nature is sacred or the value of the oneness of God, 3) reason is a process of critical thinking power with rationality methodology. 4) qalb the final filter process of the thinking process in other words self-purity. 5) nafs tends towards positive morals with proper and accurate control. The development strategy is through education, teaching, ta'dib and training. Meanwhile, the relevance of human potential is to produce integrated scientific curriculum products.